Odroczony podatek dochodowy w przedsiębiorstwie - Luty, Piotr (Deferred Income Tax in Companies, 2007)
The aim of this article is to show the importance and a place of deferred income tax in company's accountancy. The article presents also methods of estimating the total amount of differed income tax. Some managing directors have a tendency to oversimplify accounting policy so that deferred tax liabilities and deferred tax assets are not recognised. Therefore, the whole accountancy of many companies becomes only "tax accountancy system". Companies are keen on recognising future "tax benefits" and they try to avoid recognising future "tax non-benefits". This situation causes that the view of companies is not true.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 115-130